Needle in a haystack: Antibacterial activity-guided fractionation of a potato wound tissue extract. Issue 9 (1st May 2020) - Perez Rodriguez, Mathiu; Dastmalchi, Keyvan; Yoo, Barney; Stark, Ruth E.
Graphical abstract: Highlights: The most potent antibacterial fractions from the Atlantic potato wound tissue extract contained the glycoalkaloid α-chaconine in high abundance. α-Chaconine had the same minimum inhibitory concentration (MIC) as the ampicillin antibiotic, but feruloyl putrescine and ferulic acid showed lower MIC values. α-Chaconine, feruloyl putrescine, and ferulic acid potentiated ampicillin's antibacterial effects. Pairs of these compounds demonstrated synergistic and additive antibacterial effects that suggest a rationale for tuber defense directly after wounding. Abstract: Erwinia carotovora is a major cause of potato tuber infection, which results in disastrous failures of this important food crop. There is currently no effective antibiotic treatment against E. carotovora . Recently we reported antibacterial assays of wound tissue extracts from four potato cultivars that exhibit a gradient of russeting character, finding the highest potency against this pathogen for a polar extract from the tissue formed immediately after wounding by an Atlantic cultivar. In the current investigation, antibacterial activity-guided fractions of this extract were analyzed by liquid chromatography-mass spectrometry (LC-MS) utilizing a quadrupole-time-of-flight (QTOF) mass spectrometer. The most active chemical compounds identified against E. carotovora were: 6-O-nonyl glucitol, Lyratol C, n -[2-(4-Hydroxyphenyl)] ethyldecanamide, α-chaconine and α-solanine. Interactions among the three compounds, ferulic acid, feruloyl putrescine, and α-chaconine, representing metabolite classes upregulated during initial stages of wound healing, were also evaluated, offering possible explanations for the burst in antibacterial activity after tuber wounding and a chemical rationale for the temporal resistance phenomenon.